Phase Variation Leads to the Misidentification of a Neisseria Gonorrhoeae Virulence Gene - Anderson, Mark T. (Public Library of Science, 2013)
Neisseria gonorrhoeae is the causative agent of gonorrhea and an obligate pathogen of humans. The Opa proteins of these bacteria are known to mediate attachment and internalization by host cells, including neutrophils. The Opa protein repertoire of a typical N. gonorrhoeae isolate is encoded on ∼11 genes distributed throughout the chromosome and is subject to stochastic changes in expression through phase variation. Together, these characteristics make Opa proteins a critical yet unpredictable aspect of any experimental investigation into the interaction of N. gonorrhoeae with host cells. The goal of this study was to identify novel virulence factors of N. gonorrhoeae by assessing the contribution of a set of uncharacterized hydrogen peroxide-induced genes to bacterial survival against neutrophil-mediated killing. To this end, a strain harboring an engineered mutation in the NGO0322 gene was identified that exhibited increased sensitivity to neutrophil-mediated killing, enhanced internalization by neutrophils, and the ability to induce high levels of neutrophil-generated reactive oxygen species. Each of these phenotypes reverted to near wild-type levels following genetic complementation of the NGO0322 mutation. However, after immunoblot analysis of Opa proteins expressed by the isogenic parent, mutant, and genetically complemented strains, it was determined that phase variation had resulted in a disparity between the Opa profiles of these strains. To determine whether Opa phase variation, rather than NGO0322 mutation, was the cause of the observed neutrophil-related phenotypes, NGO0322 function was investigated in N. gonorrhoeae strains lacking all Opa proteins or constitutively expressing the OpaD variant. In both cases, mutation of NGO0322 did not alter survival of gonococci in the presence of neutrophils. These results demonstrate the importance of controlling for the frequent and random variation in Opa protein production by N. gonorrhoeae when investigating host cell interactions.